The Existence of a Salaf Pesantren in the Ki Ageng Tarub Grave Area in the Industrial Revolution 4.0 Era. - Sariyani, Sariyani; Prasetyo, Nova Tri (Jurnal Progress: Wahana Kreativitas dan Intelektualitas, 2024)
AbstractSalaf Pesantren, which are often connoted as traditional educational institutions, certainly carry a stigma for most people in the digital era. However, in Tarub Village the existence of a Salaf Pesantrenis a symbol of the existence of the community itself. This research aims to explore the existence of Salaf Pesantren in the Ki Ageng Tarub Grave Area in the Era of Industrial Revolution 4.0. This research uses qualitative research with a case study approach. Research data was obtained through observation, documentation and interviews with: 5 kyai, 20 santri, 13 people in 5 Pesantren. Data analysis was carried out by grouping, sorting, coding, looking for themes that were in accordance with the research objectives for later interpretation. The research results show that as a religious tourism village, Tarub Village is culturally very supportive of the development of Pesantren to further strengthen its status. Therefore, Pesantren in the Ki Ageng Tarub Tomb Area were able to develop in two forms: 1) Pesantren integrated with madrasas, 2) Pesantren only as a place to recite the Koran. This of course is able to foster a relationship of mutual influence between the Pesantrenand the Tarub Village community, both culturally, religiously and economically. So this study of Pesantren can be used as a reference for developing Pesantren based on the power of local wisdom.